The role of other financial intermediaries in monetary and credit developments in the euro area - Philippe Moutot (European Central Bank (ECB), 2007)
Monetary growth has increased significantly in the euro area in recent years, raising concerns about the risks to price stability. Viewed from a sectoral perspective, this increase reflects to a large extent the deposit holdings of other financial intermediaries (OFIs). This paper presents analytical work on the role of OFIs in monetary and credit developments in the euro area. Although, at the moment, some shortcomings in the data available – such as the lack of long time series data – seriously limit the analysis of the role of OFIs in monetary and credit aggregates, it seems clear that OFIs have gained considerable importance in recent years, not only as a factor affecting monetary developments, but also for the functioning of the financial system. This gain in importance may be due to financial deregulation and liberalisation, as well as financial innovation. These developments are reflected in the integration and deepening of euro area financial markets, as well as in investors' attitude to risk.
Keywords: 330; Finanzintermediation; Geldmarkt; Kredittheorie; Eurozone; EU-Staaten